THE DIFFERENCE BETWEEN SYNCHRONOUS AND ASYNCHRONOUS ONLINE LEARNING COMMUNICATION DURING COVID-19 PANDEMIC - Muji Endah Palupi (STIBA IEC JAKARTA, 2022)
Online learning is available in various ways and methods. To find out the difference between online communication and material presented, it must be appropriate so that it can be well received by students. For that, every university must prepare well. Learning online communication that is not ready can automatically disrupt the course of teaching and learning activities. Differences in Synchronous and Asynchronous Online Learning Communication. Synchronous communication is a learning communication carried out in a real time communication system. Lecturers can deliver material in class directly to students. Synchronous online, lecturers can still do virtual learning by online class media. Asynchronous communication is learning communication that is not limited in time. In the meaning lecturer provides material that can be used as a reference for students. The material can be learn by students in the form of PPT files, PDFs, and videos. The Covid-19 pandemic has affected almost all aspects of human life, to break the chain of virus transmission, Indonesian government take of health protocol regulations. The condition of education has huge impact. However, education must continue. Learning process during in emergency is carried out by Synchronous and Asynchronous learning